High-performance asymmetric micro-supercapacitors based on electrodeposited MnO2 and N-doped graphene. (25th March 2019) - Wang, Na; Liu, Jinzhang; Zhao, Yi; Hu, Mingjun; Shan, Guangcun
Abstract: In-plane asymmetric micro-supercapacitors using nitrogen-doped graphene (NG) film as negative electrode and MnO2 nanostructures as positive electrode are fabricated onto a plastic substrate coated with Ni/Cu film. A laser-scribing machine is employed to make interdigital finger electrodes in the plastic substrate coated with NG film via a slurry coating process. MnO2 nanosheets are electrochemically deposited onto pre-coated NG film. In LiCl-based gelled electrolyte, the NG//MnO2 cell exhibits excellent electrochemical performance and a broad voltage window up to 1.8 V. The maximum specific capacitance of a single cell is measured to be 13 mF cm −2 . In addition, several cells in series can be easily fabricated by combining the laser-scribing technique and the electrodeposition of MnO2 electrodes. As a proof of concept, four cells in a compact configuration and with high voltage output up to 7.2 V are demonstrated.